Valorization of pomegranate peels: a biorefinery approach - Pathak, P. D.; Mandavgane, S. A.; Kulkarni, B. D. (Waste and Biomass Valorization, 2017)
Recent studies have shown that pomegranate peels (PP) is a valuable source of valuable bioactive compounds, most of which can be converted into value-added products. We herein review this conversion process and provide an outline on the chemical composition of PP and the possible value-added products that can be produced from this commonly discarded agro-waste. We have also discussed its use as a substrate to produce medicinal compounds and bioactive phenolic compounds (e.g., phenolic acids, flavonoids, vitamin C, fertilizers, dietary fibers, and tannins) as well as its use in nanomaterial synthesis. Based on available evidence, it is obvious that PP has a wide variety of applications, and thus, developing an efficient system to utilize PP adequately will help to completely utilize its potential benefits. The biorefinery approach shows promising potential for efficient utilization of PP; however, additional studies should be conducted in this area. © 2016, Springer Science+Business Media Dordrecht.

Valorization of potato peel: a biorefinery approach - Pathak, P. D.; Mandavgane, S. A.; Puranik, N. M.; Jambhulkar, S. J; Kulkarni, B. D. (Critical Reviews in Biotechnology, 2017)
Potato is the fourth main crop consumed worldwide and is an important constituent in the human diet. Consequently, potato is widely used in food-processing industries. However, these industries generate massive amounts of potato peel (PP) as a by-product, which is usually considered a waste, and is discarded. Interestingly, recent research suggests that PP is a valuable source of bioactive compounds, which can be converted into value-added products. In this study, we review the physicochemical composition and valorization of PP. In addition to being used as a dietary fiber or medicine, the value-added products obtained by the fermentation of PP have multiple uses, including their use as adsorbents, biocomposites and packaging materials. These products can also be used in energy production, biopolymer film development, corrosion inhibition and the synthesis of cellulose nanocrystals. The biorefinery approach for PP will increase the value of this waste by producing an array of value-added products and reducing extensive waste generation.
Keywords: Bioactive compounds; Biorefinery; Potato peel; Valorization; Value-added products

Process of fruit peel waste biorefinery: a case study of citrus waste biorefinery, its environmental impacts and recommendations - Joglekar S.N.; Pathak, P. D.; Mandavgane, S. A.; Kulkarni, B. D. (Environmental Science and Pollution Research, 2019)
Fruit peels are a rich source of cellulose, hemicellulose, phenolic compounds, and terpenic compounds. Thus, they have the potential to be a novel renewable, sustainable, and low-cost raw material (source) for the production of several value-added products based on framework and concepts such as waste hierarchy that includes biofertilizers, dietary fiber, animal feed, industrial enzymes, substrate for the bioactive compounds production, synthesis of nanomaterials, and clean energy (from residual biomass). With a view of evaluating the environmental burden of biorefinery, a life cycle assessment (LCA) is performed for a representative citrus waste (CW) biorefinery. The functional unit used for LCA was set as 2500 kg of CW processed. The overall GWP was observed to be 937.3 kg CO2 equivalent per 2500 kg of CW processed. On further analysis of the environmental impact, it was found that different steps contributed significantly, as shown by the various environmental indicator values. Alternative advanced process intensification technologies like microwave and ultrasound-assisted steps replacing the conventional steps when implemented show considerable reduction in environmental indicator values. The variations in the contribution to environmental indicators should be considered during the design and process selection of biorefineries.